Formulation development of lipid polymer hybrid nanoparticles of doxorubicin and its in-vitro, in-vivo and computational evaluation - Shafique, Muhammad; Ur Rehman, Maqsood; Kamal, Zul; Alzhrani, Rami M.; Alshehri, Sameer; Alamri, Ali H.; Bakkari, Mohammed Ali; Sabei, Fahad Y.; Safhi, Awaji Y.; Mohammed, Ahmed M.; Hamd, Mohamed A. El; Almawash, Saud (Frontiers in Pharmacology, 2023)
The purpose of our research work was to assess the formulation development parameters of doxorubicin (DOX) loaded lipid polymer hybrid nanoparticles (LPHNs) in rabbit model to evaluate the intrinsic outcome of the dosage form improvement after oral administration. LPHNs were prepared by combine approach, using both magnetic stirring and probe sonication followed by characterization in terms of size-distribution (Zeta Size), entrapment efficiency (EE), loading capacity, and the kinetics of Doxorubicin. The lyophilized LPHNPs were also characterized by scanning electron microscopy (SEM), powder X-Ray diffractometry (P-XRD), Fourier transformed infrared (FT-IR and differential scanning calorimetry (DSC) etc. The molecular modeling was determined through density functional theory (DFT) simulations and interactions. DOX and Doxorubicin-lipid polymer hybrid nanoparticles (LPHNs) were administered orally to rabbits. The plasma concentration of Doxorubicin was determined using high performance liquid chromatography (HPLC). The average size of Doxorubicin loaded LPHNs was 121.90 ± 3.0 nm. The drug loading of Doxorubicin was 0.391% ± 0.01 of aqueous dispersion, where its encapsulation efficiency was 95.5 % ± 1.39. After oral administration of DOX- LPHNs, the area under the plasma concentration-time curve (AUC) was meaningly improved (about 2-fold) in comparison to the control group (p < 0.05). Density functional theory simulations were used to understand the interactions of polymers with different sites of Doxorubicin molecule. The larger negative binding energies (-9.33 to -18.53 kcal/mol) of different complexes evince that the polymers have stronger affinity to bind with the Doxorubicin molecule while the negative values shows that the process is spontaneous, and the synthesis of DOX-LPHNs-is energetically favorable. It was concluded that DOX-LPHNs-provided a promising new formulation that can enhance the oral bioavailability, optimized polymer compatibilities and improve pharmacokinetic of Doxorubicin after oral administration.